Potencial antibacteriano do óleo essencial de Melaleuca alternifolia (Maiden & Betche) Cheel e desenvolvimento de filmes ativos para aplicação em alimentos - Cunha, Kamila Furtado (2019)
For the control of pathogens in food, alternative methods to exploit the potential of natural extracts, such as essential oils (OE), are considered promising for different applications, since these compounds present several biological properties, such as the antibacterial action. Among these applications, it is sought the development of active packaging, using biodegradable matrices, such as cellulose acetate, in order to minimize impacts to the environment, due to the accumulation of synthetic polymers. Therefore, the objective of the study was to develop cellulose acetate films incorporated with OE from Melaleuca alternifolia (Maiden & Betche) Cheel (OETT) and to evaluate its antibacterial potential for food application. The antibacterial action of OETT was evaluated in vitro by disc diffusion, minimum inhibitory and bactericidal concentration against Listeria monocytogenes ATCC 7644, Staphylococcus aureus ATCC 25923, Escherichia coli O157: H7 NCTC 12900 and Salmonella Typhimurium ATCC 14028 and thereafter films were made with OETT , and T1 treatments with 2xCIM (1.56% for isolates and 3.2% for S. Typhimurium ATCC 14028) and T2 with 4xCIM (3.2% for isolates and 6.4% for S. typhimurium ATCC 14028), and a non-OE film, which were evaluated in vitro against the same pathogens by disc diffusion and stock kinetics in broth. Then the active films were evaluated in situ using sliced baked ham. As results, it was observed that OE demonstrated in vitro action against all pathogens evaluated, with S. Typhimurium being more sensitive to the action of the films, and its action against food isolates was also evaluated. In the in vitro assays, the multidrug resistant Salmonella spp. was shown to be more sensitive to films with incorporated OE when compared to the susceptible isolate and the standard strain. It was observed that in the in situ evaluation, from the first day of exposure of the contaminated food matrix to the films, both for T1 and T2, it was observed that there was no growth of any of the bacteria evaluated in the study, demonstrating a bactericidal action. Thus, it is concluded that the OE of M. alternofolia (Maiden & Betche) Cheel presents an antibacterial action against different food pathogens, and when applied in acetate films, are effective in the control of Salmonella spp. in ham.